Role of the Principal as a Leader for Crisis Management in Primary Schools in Mexico - Rubi Alejandra Medrano-Chan; Liz Hollingworth; Pedro Antonio Sánchez-Escobedo (International Journal of Educational Leadership and Management, 2025)
This work explores perceptions of both principals and teachers regarding the leader role and readiness of three Mexican primary school principals to manage critical events in their schools in the state of Yucatán. The study focusses on school communities embedded in disadvantageous social contexts characterized by poverty, family dysfunction, and violence as well as threats from natural disasters like hurricanes. Throughout in-depth interviews, principals expressed their concerns about their responsibilities and identified vulnerabilities in the case of a crisis in the school. Likewise, through focus groups we collected information on how teachers perceived the role of their principals in a crisis and their expectations and problem-solving skills in such situations. The main findings are that principals recognize the leadership they must have to resolve crises and understand they are responsible for the safety and well-being of students and the barriers they have encountered in these situations included the social context surrounding the school, institutional regulations, and a lack of training for crisis management. Specific competencies identified by the teachers for crisis management included informed decision-making, good communication, and acting quickly. Findings provide the basis for discussing the role of principals as leaders in a crisis, identifying specific training and communication requirements.